Kinerja Supervisor dan Kepala Madrasah dalam Meningkatkan Kualitas Pendidikan Agama Islam di Kota Yogakarta - Hamidah Triwinarsih (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2021)
This research aims to determine the performance of supervisors and madrasah heads in improving the quality of Islamic Religious Education in Yogyakarta through supervision activities. This study is also to find out whether there are performance differences between supervisors and madrasah heads. This research uses quantitative methods. Data collected through questionnaires, document studies conducted to match the data of the results of the questionnaire. The analysis methods used in this study are variant analysis and advanced testing. The results showed that; (1) supervisor performance in improving the quality of education reached 90.47% was in a very good position, (2) the performance of madrasah head as supervisor reached 80.11% was in a good position, (3) there was no difference in supervisor performance in the preparation, implementation and evaluation of the program, while the performance of supervisors in guiding teacher professionals there was a significant difference, (4) there was no difference in the performance of the head of MI in Yogyakarta, while the performance of mts head there was a significant difference. Similarly, with the performance of the head of MA in Yogyakarta there are significant differences, (5) there is no difference in the learning outcomes of MI students in Yogyakarta, while the learning outcomes of MTs and MA students are quite significant differences.